A serological survey on bulls of an artificial insemination centre for infectious bovine rhinotracheitis (IBR) virus neutralising antibodies - ΠΑΠΠΟΥΣ, Χ.; ΔΗΜΗΤΡΙΑΔΗΣ, Ι.; ΠΟΙΛΑΣ, Σ.; ΚΑΡΑΤΖΑΣ, Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The results of periodical serological examinations of bulls in an Artificial Insemination Centre for antibodies neutralising IBR virus, during the period 1978-81 are given. 155 serum samples belonging to 45 animals of this centre were tested. 29 sera were found positive (18.9%) coming from 13 animals. The percentage by year of the IBR infection varied from 14.8 to 25%. Except one clinical case of IBR the other positive animal did not show apparent disease.